Sanksi Hukum terhadap Penyebaran Konten Radikalisme di Internet dalam Perspektif Undang-Undang Terorisme di Indonesia - Nendriana Sistia Kusuma; Yasarman Yasarman (Decisio: Jurnal Ilmiah Hukum, 2025)
The rapid growth of internet usage in Indonesia has accelerated information dissemination while enabling the spread of radical content that threatens national security. Social media serves as an effective platform for extremist groups to promote their ideology, making online radicalization an increasingly serious concern. The government has addressed this issue through Law No. 5 of 2018 on Terrorism and the Electronic Information and Transactions Law (ITE Law). However, implementation remains challenging, particularly in defining “radical content” and overcoming technological barriers in law enforcement. This study employs a qualitative method with a normative legal approach, focusing on regulatory analysis and interpretation of existing norms through literature review of primary, secondary, and tertiary legal materials. The findings indicate that despite an existing legal framework, enforcement is hindered by unclear definitions and detection difficulties on encrypted platforms. Regulatory reform and preventive strategies, such as digital literacy and state–platform collaboration, are essential to curb online radicalization effectively.